Contingency and breakdown: children with SLI and their conversations with mothers and fathers - Conti-Ramsden, G; Hutcheson, G D; Grove, J (Journal of speech and hearing research, 1995)
The present study aimed to investigate the nature and frequency of parental recasts (both mothers and fathers) to children with SLI as compared to normal language learning children of the same language stage including their younger siblings. The comparisons were made within the framework of discourse function to include behaviors related to conversational contingency and conversational breakdown. Results showed that children with SLI at the early stages of development experience a simple recast gap in their linguistic input. Qualitative differences in the context in which recasts occurred were also noted. Furthermore, some differences between mothers and fathers were found. These findings are discussed in light of previous research with particular reference to the Rare Event Theory and the Bridge Hypothesis.